SV2A PET imaging in human neurodegenerative diseases - Bavarsad, Mahsa Shanaki; Grinberg, Lea T. (Frontiers in Aging Neuroscience, 2024)
This manuscript presents a thorough review of synaptic vesicle glycoprotein 2A (SV2A) as a biomarker for synaptic integrity using Positron Emission Tomography (PET) in neurodegenerative diseases. Synaptic pathology, characterized by synaptic loss, has been linked to various brain diseases. Therefore, there is a need for a minimally invasive approach to measuring synaptic density in living human patients. Several radiotracers targeting synaptic vesicle protein 2A (SV2A) have been created and effectively adapted for use in human subjects through PET scans. SV2A is an integral glycoprotein found in the membranes of synaptic vesicles in all synaptic terminals and is widely distributed throughout the brain. The review delves into the development of SV2A-specific PET radiotracers, highlighting their advancements and limitations in neurodegenerative diseases. Among these tracers, 11C-UCB-J is the most used so far. We summarize and discuss an increasing body of research that compares measurements of synaptic density using SV2A PET with other established indicators of neurodegenerative diseases, including cognitive performance and radiological findings, thus providing a comprehensive analysis of SV2A's effectiveness and reliability as a diagnostic tool in contrast to traditional markers. Although the literature overall suggests the promise of SV2A as a diagnostic and therapeutic monitoring tool, uncertainties persist regarding the superiority of SV2A as a biomarker compared to other available markers. The review also underscores the paucity of studies characterizing SV2A distribution and loss in human brain tissue from patients with neurodegenerative diseases, emphasizing the need to generate quantitative neuropathological maps of SV2A density in cases with neurodegenerative diseases to fully harness the potential of SV2A PET imaging in clinical settings. We conclude by outlining future research directions, stressing the importance of integrating SV2A PET imaging with other biomarkers and clinical assessments and the need for longitudinal studies to track SV2A changes throughout neurodegenerative disease progression, which could lead to breakthroughs in early diagnosis and the evaluation of new treatments.